Fed and ECB: Which is informative in determining the DCC between bitcoin and energy commodities? - Abdelkader Derbali; Lamia Jamel; Monia Ben Ltaifa; Ahmed K. Elnagar; Ali Lamouchi (Journal of Capital Markets Studies (JCMS), 2020)
Purpose This paper provides an important perspective to the predictive capacity of Fed and European Central Bank (ECB) meeting dates and production announcements for the dynamic conditional correlation (DCC) between Bitcoin and energy commodities returns and volatilities during the period from August 11, 2015 to March 31, 2018. Design/methodology/approach To assess empirically the unanticipated component of the US and ECB monetary policy, the authors pursue the Kuttner's approach and use the federal funds futures and the ECB funds futures to assess the surprise component. The authors use the approach of DCC as introduced by Engle (2002) during the period from August 11, 2015 to March 31, 2018. Findings The authors' results suggest strong significant DCCs between Bitcoin and energy commodity markets if monetary policy surprises are incorporated in variance. These results confirmed the financialization of Bitcoin and commodity energy markets. Finally, the DCC between Bitcoin and energy commodity markets appears to respond considerably more in the case of Fed surprises than ECB surprises. Originality/value This study is a crucial topic for policymakers and portfolio risk managers.
Keywords: E52; E63; O13; Q02; 330; Bitcoin; DCC; Energy commodities; Monetary policy surprises